The Adaptation of the Novel Mawlānā into the Film Mawlānā: The Preacher by Ibrāhīm ʿĪsā - Nurul Izzati, Maila; Supriadi, Dedi; Khomisah (Al-Ma‘rifah, 2025)
This comparative Ekranisasi study analyzes the ideological negotiation and power relations inherent in adapting Ibrāhīm ʿĪsā’s 2012 novel Mawlānā (a critique of the religion-state-media nexus) into Magdi Ahmad Ali’s 2016 film, Mawlānā: The Preacher. The novel centers on protagonist Sheikh Ḥātim's profound spiritual hypocrisy and moral crisis, yet the film shifts focus toward rapid socio-political dynamics, sacrificing the protagonist’s complex psychological depth. This research addresses the core question of whether this reduction of moral depth was dictated by cinematic necessity or an ideological compromise with political pressure and censorship. Utilizing a qualitative, interpretive methodology extending Pamusuk Eneste's structural framework, the study adds a crucial interpretive layer analyzing ideologically motivated changes. Findings confirm the film sacrificed the novel’s complex moral tragedy by drastically reducing sensitive narrative pillars (e.g., critique of elite corruption, sexual/psychological trauma). This politically driven sanitization fundamentally transformed the work into a socio-political drama. The study’s theoretical contribution is significant: the categorization of adaptational changes (reduction, addition) cannot be detached from the context of ideological production. Specifically, in sensitive political contexts, narrative reduction primarily functions as a strategy of self-censorship and political negotiation, rather than mere technical condensation.